Effects of spatiotemporal constraints and age on the interactions of soccer players when competing for ball possession - Menuchi, M. R. T. P.; Moro, A. R. P.; Ambrósio, P. E.; Pariente, C. A. B.; Araújo, D. (Journal of Sports Science & Medicine, 2018)
Although there are several descriptions of interpersonal coordination in soccer teams, little is known about how such coordination is influenced by space and time constraints. In this study, we analyzed variations in interpersonal coordination under different marking intensities and across different age groups. Marking intensity was manipulated by changing the players` game space and time of ball possession in a conditioned soccer game known as rondo. Five participants in each age category (U13, U15, U17, and U20) performed rondo tasks in four experimental conditions, in a total of 134 trials. The dependent variables considered were pass performance and eco-physical variables capturing the player-environment coupling, such as coupling of the marking between players. Our results demonstrate that in soccer: (1) markers and passers are tightly coupled; (2) the marker-passer coupling emerges from a flexible and adaptive exchange of passes; (3) the marker-passer coupling is stronger in markings of higher intensity and older age groups. Thus, the interactions between soccer players in marking can be analyzed as an emerging and self-organized process in the context of group performance.